2015
DOI: 10.1097/mou.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

A genetic-based approach to personalized prostate cancer screening and treatment

Abstract: Purpose Recent advances in sequencing technologies has allowed for the identification of genetic variants within germline DNA that can explain a significant portion of the genetic underpinnings of prostate cancer. Despite evidence suggesting that these genetic variants can be used for improved risk stratification, they have not yet been routinely incorporated into routine clinical practice. This review highlights their potential utility in prostate cancer screening. Recent Findings There are now almost 100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…Despite evidence suggesting that these genetic variants can be used for improved risk stratification, they have not yet been routinely incorporated into routine clinical practice. Next to several original publications[58, 59], Helfand et al 60] reviewed their potential utility in PC screening and claim that it is possible that SNPs analyses can help risk stratify men who have increased susceptibility and target PSA based screening only to those men who are at increased risk. Same holds for SNPs that are strongly associated with PSA levels (so-called PSA-SNPs).…”
Section: Methodsmentioning
confidence: 99%
“…Despite evidence suggesting that these genetic variants can be used for improved risk stratification, they have not yet been routinely incorporated into routine clinical practice. Next to several original publications[58, 59], Helfand et al 60] reviewed their potential utility in PC screening and claim that it is possible that SNPs analyses can help risk stratify men who have increased susceptibility and target PSA based screening only to those men who are at increased risk. Same holds for SNPs that are strongly associated with PSA levels (so-called PSA-SNPs).…”
Section: Methodsmentioning
confidence: 99%
“…Certain molecular markers have also been linked to the clinical course and disease outcomes in men with prostate cancer [26,27]. For instance, several studies have identified multiple single nucleotide polymorphisms (SNPs) that are preferentially expressed in African-Americans [27]. Approximately 100 genes containing SNPs have been linked to an increased susceptibility to prostate cancer [27].…”
Section: Molecular Markersmentioning
confidence: 99%
“…For instance, several studies have identified multiple single nucleotide polymorphisms (SNPs) that are preferentially expressed in African-Americans [27]. Approximately 100 genes containing SNPs have been linked to an increased susceptibility to prostate cancer [27]. Single nucleotide polymorphisms are especially valuable in disease detection, monitoring, and screening because they are stable throughout the lifetime of the individual and are not affected by external factors, such as lifestyle [27].…”
Section: Molecular Markersmentioning
confidence: 99%
“…Despite extensive efforts in developing novel biomarkers in this regard, no single biomarker can accurately predict the aggressiveness of this cancer thus far [15]; largely due to the heterogeneous properties of prostate cancers between individual patients and/or even among different loci within a given tumor mass [3]. By recognizing the distinct genetic differences between patients [16], personalized medicine is emerging as a new strategy for prostate cancer management. Still, adequate biomarkers are needed to determine tumor aggressiveness.…”
Section: A Prostate Cancer Managementmentioning
confidence: 99%